2013
DOI: 10.1044/1092-4388(2012/12-0075)
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude Rise Time Does Not Cue the /bɑ/–/wɑ/ Contrast for Adults or Children

Abstract: Purpose Previous research has demonstrated that children weight the acoustic cues to many phonemic decisions differently than do adults and gradually shift those strategies as they gain language experience. However, that research has focused on spectral and duration cues rather than on amplitude cues. In the current study, the authors examined amplitude rise time (ART; an amplitude cue) and formant rise time (FRT; a spectral cue) in the /bɑ/–/wɑ/ manner contrast for adults and children, and related those speec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 44 publications
1
38
2
Order By: Relevance
“…For example, Nittrouer and Studdert-Kennedy (1986) switched ARTs across syllable types using natural speech tokens and found that adults continued to label consonants based on FRT. Both Walsh and Diehl (1991) and Nittrouer, Lowenstein, and Tarr (2013) replicated those results using synthetic stimuli, which provides an important control. In natural speech, fundamental frequency differs between the two consonantal contexts and could serve as another cue to consonant identity.…”
Section: Evaluating Cue Weighting In Adults With Cis Using the /Bɑ/-/supporting
confidence: 59%
See 1 more Smart Citation
“…For example, Nittrouer and Studdert-Kennedy (1986) switched ARTs across syllable types using natural speech tokens and found that adults continued to label consonants based on FRT. Both Walsh and Diehl (1991) and Nittrouer, Lowenstein, and Tarr (2013) replicated those results using synthetic stimuli, which provides an important control. In natural speech, fundamental frequency differs between the two consonantal contexts and could serve as another cue to consonant identity.…”
Section: Evaluating Cue Weighting In Adults With Cis Using the /Bɑ/-/supporting
confidence: 59%
“…In the current study, the same stimuli as those used by Nittrouer et al (2013) were presented to adults with CIs, and perceptual weighting strategies were indexed using calculated weighting factors. For illustrative purposes, Figure 2 shows labeling functions for adults with normal hearing in that study, obtained with two complementary sets of stimuli.…”
Section: Indexing the Weights Assigned To Acoustic Cuesmentioning
confidence: 99%
“…However, our data were also in agreement with work showing that in the presence of neutral formant transition information, listeners with normal hearing were able to shift to use of temporal envelope information (Hedrick & Younger, 2001). Note that recent work by Nittrouer and colleagues (2013) drew a different conclusion, in that their adult listeners with normal hearing did not use envelope cues at all. That finding can be explained by considering Nittrouer’s stimuli, in which the formant transition was either typical of /ba/ or typical of /wa/ but never neutral.…”
Section: Discussionmentioning
confidence: 92%
“…Those data are in good agreement with earlier work showing that normal-hearing listeners have full capability of using formant transitions (Carpenter & Shahin, 2013; Hedrick & Younger, 2001, 2007; Lindholm et al, 1988). When both cues were present for listeners with normal hearing, perceptions were impacted by formant transition information to a greater extent than temporal (envelope) cues (e.g., Nittrouer, Lowenstein, & Tarr, 2013). The difference between listeners with hearing loss and normal hearing was dramatic; compare Figures 5 and 9, which show the heavy use of temporal cues by listeners with hearing impairment.…”
Section: Discussionmentioning
confidence: 98%
“…Although a software algorithm originally estimated boundaries, all were checked by eye subsequently. Once voiced signal portions were identified, individual pitch periods were located, using the method described by Nittrouer et al (2013). The fundamental frequency associated with each pitch period was derived by taking the inverse of the period.…”
Section: Stimulimentioning
confidence: 99%